STUDY OF TRENDS IN THE ETIOLOGICAL STRUCTURE OF NOSOCOMIAL INFECTIONS BEFORE AND DURING THE COVID-19 PANDEMIC IN THE RUSE REGION FOR 2017-2021 - Daniel Monov; Tsonko Paunov (Peytchinski Publishing, 2023)
The most important and very difficult thing is to establish the cause (etiology) for the occurrence of nosocomial infections in medical facilities in the country and the world. Objective: To study the frequency and structure of nosocomial infections before and during the Covid-19 pandemic in the Ruse region for 2017-2021. Materials and methods: A retrospective analysis of the data on the registered nosocomial infections for a period of five years (2017 - 2021), reports, analyses, and laboratory studies of Regional Health Inspectorate Ruse, from national governmental studies, normative documents and literature are applied. Results: The analysis of the data from the etiological diagnosis of nosocomial infections in the Ruse region is from 9 medical facilities included in the national electronic system for the control of nosocomial infections (NIs). The etiological structure of NIs in the Ruse region is represented by 39 microbial species. The relative share of the untested varies from 10.59% in 2017 to 15.75% in 2021. For the etiologically unproven, it is from 2.39% for 2019 to 1.68% for 2021, with a decreasing trend. Conclusions: The analysis of the isolated microbial species by group shows that for the entire period, the proportion of gram-negative flora was 62% of the isolates (2017), followed by 23.02% of gram-positive microorganisms (2017), and the relative proportion of fungi and viruses was ~ 3 %.